Structural integrity assessment of rail steel failure modes and mechanism - Liu, Yang (Nanyang Technological University, 2021)
Rail steels are susceptible to fatigue failures resulting in rail breaks that can lead to unplanned downtime and safety concerns in railway operations. The main concern of the structural integrity in the rail track system is rail breaks resulting from fatigue failures of continuously welded rail structures, particularly, the thermite welded rail joints. The objective of this research is to study the fatigue structural integrity behaviour and fracture mechanics properties of the thermite welded rail joints. The thermite welded rail joint, particularly the weld-toe region, is susceptible to fatigue crack formation. This is because of reasons as a) the geometry irregularities of the weldment at the weld toe region, b) the local weakness of metallurgical properties across the welded joint, and c) the presence of high tensile residual stress arising from the welding process. These three reasons interact with each other, affect the fatigue mode at the weld toes and deteriorate the fatigue endurance of the thermite welded rail joints. In this research, a range of techniques and procedures were adopted to develop a framework for structural integrity assessment in three main areas of interest. Firstly, the fatigue behaviour of the welded joint with respect to the weldment geometry profile variation was studied using Fracture Mechanics. The stress intensity factor solutions were determined through finite element analysis and presented by the geometry factor, and weld magnification factor, k. Secondly, the mechanical and fatigue properties, and the size and distribution of weld defects were characterized. Transverse weld-toe surface cracks at the fusion line of the welded joint are found to be caused by the high density of weld defects and the mismatch of strength and fatigue properties between the thermite weld metal and unaffected rail steel. Lastly, a three-dimensional finite element model including the sequentially coupled thermal-mechanical simulation and cyclic plasticity constitutive simulation was developed to investigate the welding process-induced tensile residual stress and the redistribution of the residual stresses due to cyclic bend fatigue loading, respectively. The numerical results of the finite element model were compared with experimental residual stress measurement data. A structural integrity assessment methodology of the thermite welded rail joint with the analytical discussion of the underlying fatigue failure mechanism and the quantitative evaluation of fatigue propagation life was developed. The factors on the risk of fatigue failures at a given stress level, such as the variation in geometry profile, material discontinuities, and tensile residual stresses from the welding process, were also discussed. The structural integrity is established by providing a reliable Fracture mechanics-based fatigue model to predict the fatigue propagation life of the weld-toe transverse surface cracks at specific locations under the given sets of loading conditions.